Implementasi Manajemen Strategik Kepala Madrasah Untuk Menghadapi Era Revolusi 4.0 - Sari, Meiliza; Fadhil, Muhammad; Amin, Muhammad (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
The purpose of this study was to determine the implementation of the strategic management of madrasah principals to face the era of the industrial revolution 4.0 at MAN 1 Pekanbaru. This type of research is descriptive qualitative research, the subject of this research is the head of the madrasa while the object is strategic management. Research data were collected using interview and documentation techniques. Data analysis using data collection, data reduction, data presentation, and drawing conclusions. The results of this study are 1) the head of the madrasah conducts a work meeting at the beginning of the year with all madrasa stakeholders, formulates a strategy by considering the internal and external factors of the madrasa; 2) Making Madrasah Self-Evaluation; 3) Make madrasa residents commit from the start not to run away from planning; 4) Vision, mission, expectations of goals and objectives that go international; 5) Involve all madrasah residents to take an active role; 6) Using the concept of the right man on the right place; 7) Educators and education staff are able to master technology; 8) Carry out continuous supervision directly and indirectly; 9) Delegation of authority in supervision, 10) Evaluation periodically by holding regular meetings